2019
DOI: 10.1039/c9nj03576a
|View full text |Cite
|
Sign up to set email alerts
|

A superhydrophobic poly(lactic acid) electrospun nanofibrous membrane surface-functionalized with TiO2 nanoparticles and methyltrichlorosilane for oil/water separation and dye adsorption

Abstract: A superhydrophobic PLA electrospun nanofibrous membrane surface-functionalized with TiO2 nanoparticles and methyltrichlorosilane can achieve oil/water separation and methylene blue adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Several oils were tested to analyze the efficiency of the membrane; they exhibited excellent separation results, with efficacy greater than 95%. 139…”
Section: Recent Trends In Biopolymers and Their Electrospinningmentioning
confidence: 99%
“…Several oils were tested to analyze the efficiency of the membrane; they exhibited excellent separation results, with efficacy greater than 95%. 139…”
Section: Recent Trends In Biopolymers and Their Electrospinningmentioning
confidence: 99%
“…They found that the maximum adsorption capacity of ZIF-67/PAN nanofibers was 1305, 849 and 730 mg/g for MG, CR and BF, respectively. Additionally, the results confirmed that the ZIF-67/PAN nanofibers can be used more than four times for the removal of MG. Table 7 displays the adsorption data of dyes by EPNFs/silica [198], EPNFs/metal oxides [199][200][201][202][203][204] and EPNFs/MOFs nanocomposites [92,95,197]. Despite the role of MOFs in improving the ability of some EPNFs to remove some dyes from aqueous solutions, there are some challenges facing the incorporation of MOFs into EPNFs matrix.…”
Section: Epnfs/metal Oxides Nanocompositesmentioning
confidence: 99%
“…Besides, the pore size plays an important role in membrane applications in various elds from separation, adsorption to tissue engineering. 14,[31][32][33][35][36][37][38] Thus, a method for adjusting the porous structure is of high interest. Polymerization induced phase separation (PIPS) has emerged as a promising method to address these limitations as it offers the possibility to create materials with inherent, self-organized porous structure with adjustable porosity.…”
Section: Introductionmentioning
confidence: 99%